2022
DOI: 10.46989/001c.55599
|View full text |Cite
|
Sign up to set email alerts
|

Microbial-environmental interactions reveal the evaluation of fermentation time on the nutrient properties of soybean meal

Abstract: Microbial fermentation techniques are often used to improve their quality, where the keys are fermentation strains and fermentation time. This study studied the interaction between microbiota and environmental (or nutritional) factors and microbiota at different fermentation times to determine the most appropriate time, using lactic acid bacteria as fermentation strains. It can be concluded that fermentation improved the nutritional value of soybean meals. In the early stages of fermentation, debris in soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…pH and inoculum size are the other two important factors in the fermentation process of soybean meal. pH plays an important role in helping to stabilise the microbial community (Jin et al ., 2022). Studies have found that microbial fermentation produces lactic acid and that lower pH levels inhibit the growth of potentially harmful bacteria (Emkani et al ., 2022).…”
Section: Microbial Fermentation Of Soybean Mealmentioning
confidence: 99%
“…pH and inoculum size are the other two important factors in the fermentation process of soybean meal. pH plays an important role in helping to stabilise the microbial community (Jin et al ., 2022). Studies have found that microbial fermentation produces lactic acid and that lower pH levels inhibit the growth of potentially harmful bacteria (Emkani et al ., 2022).…”
Section: Microbial Fermentation Of Soybean Mealmentioning
confidence: 99%